Analysis of Sungai Ular Water Quality Viewed from The Impact of Palm Oil Industry Activities And PDAM - Kurniawan, Zahir; Agustina, Nur Ariyani; Pratomo, Bayu (Talenta Publisher, 2020)
This research aims to determined the effect of industry wastes of Palm Oil and PDAM to the river water quality use parameters of the water caracteristic, parameters that using to determine the water Pollution level as ; Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Mangan (Mn), Aluminium (Al), Besi (Fe), Timbal (Pb), turbidity, and water quality standards of Sungai Ular. This research was carried out in Sungai Ular to Serdang Bedagai Regency and Deli Serdang Regency and next in The Laboratorium Socfindo Seed Production & Laboratories (SSPL) in September - October 2020. The research method is used a Purposive sampling. At all the stations of Sungai Ular stations that have determined in this research are result of parameters from BOD are into to the class II all of stations, and concentration of COD all of stations into to the class, and another parameters are still below the threshold to all of stations so can said from averaged of parameters all of stations, the Water quality of Sungai Ular are still classified below the threshold in accordance with government regulation number 82 of 2001. Keywords: Quality, River, Pollution, Industry.